Study Of Law No.6 of 2011 on Criminal Liability of Foreigners Who Violate Their Stay Permit In Indonesia (Overstay) - Simatupang, Jeprita; Anggusti, Martono; Sihotang, Lesson (Indonesian Journal Publisher, 2025)
The purpose of this research includes the regulation of citizen residence permits in Indonesia based on the Law on Immigration and how sanctions for citizens who violate residency permits in Indonesia or commonly referred to as Overstay The research used by researchers is a type of normative juridical research (legal research), namely using the source of legal materials in the form of legislation, decisions / court provisions, legal theory, approaches from books related to legal issues that are examined. Violations committed in the form of exceeding the deadline for residence permits (overstay), are subject to deportation as a special measure of immigration, legal sanctions against citizens who do not have a residence permit through administrative measures and criminal sanctions, subject to 5 years in prison, a fine of 500 million for those who fake visas / residence permits with the intention of being used in / out of Indonesia. 6 Year 2011 on Immigration, In its implementation, immigration control is a shared responsibility between immigration officials and the public, with the investigation of immigration crimes carried out by Immigration Servant Investigators (PPNS) in coordination with the Indonesian National Police.